Inter-organizational dynamics and the ecology of localized entrepreneurship. Issue 1 (1st January 2020) - Mars, Matthew M.
ABSTRACT: In this paper, a set of ecological principles (actor-type, interaction-type, nestedness) that have been theoretically associated with organizational ecosystems guides a qualitative exploration of the ecology of localized entrepreneurial clusters (LECs). The focus of analysis is the Southern Arizona craft brewing sector (SACBS). The inter-organizational dynamic that characterizes the ecology of the SACBS is found to be based more on mutualism than on competition. This dynamic is primarily based on shared commitments to local beer brand identity, product quality, and sustainable production, as well as an overall sense of community connectedness. The SACBS is also shown to be a tightly nested LEC with craft breweries operating primarily as generalists within the local context rather than as specialists within the national and global contexts. Findings illustrate the strategic value of treating LECs as community-based sectors that are driven more by inter-organizational coordination and collaboration than by division and competition.